Studies in Sumerian Civilization. Selected writings of Miguel Civil - Lluís Feliu (ed.) (Col·lecció Barcino Monographica Orientalia, 2017)
Miguel (or Miquel) Civil's oeuvre has been unanimously acclaimed by the entire Assyriological community, from his first contributions in the 1960s to the most recent publications today. This volume gathers together his principal articles, which have been published in the most prestigious series and periodicals in the field of cuneiform studies. Every expert in the civilizations of ancient Mesopotamia has been influenced by Civil's profound researches: the perspicacity of his proposals, the novelty of his suggestions and the originality of his solutions. Cuneiform studies would be a completely different discipline were it not for the stimulus and impact of the work of a scholar who created his own school, and who will be leaving a mark on many generations to come.